Correlation between Hormonal and Biochemical Changes with Kidney Function in Newly and Previously Diagnosed Women Diseased with Polycystic Ovary Syndrome (Indian Journal of Forensic Medicine & Toxicology, 2020)
The objectives of our work was to identify the effects of insulin resistance and other hormonal changes onkidney function in newly and previously diagnosed women diseased with PCOS.Method: This prospective study was done by collect serum samples and urine from three group (Control60), (previously 50), (newly 50) patients. The withdrawal led samples were subsequently assay for hormonaland biochemical changes.Results: The data of tests were available for both groups. We found significant differences in level ofinsulin, Homeostatic model assessment Insulin resistance (HOMA-IR), Homeostatic model assessmentBeta function (HOMA-B), Progesterone among newly and previous women, also the data indicated asignificant correlation between urea and testosterone in newly while direct significant correlation betweenurea and progesterone. There was significant correlation between Thyroid stimulating hormone (TSH) andcreatinine in previously diagnosed PCOS, also direct correlation between uric acid and Body mass index(BMI), Fasting blood glucose (FBS), HOMA IR and inverse correlation with Triiodothyronine (T3) in newPCOS while in previously diagnosed PCOS there is inverse correlation between uric acid and T3. Finally,significant correlation between FBS, insulin, HOMA B and HOMA IR in previously diagnosed patientswhile correlation is seen between FBS, insulin and HOMA IR in newly patients.